Association of metabolic syndrome with complicated gall stone disease: our experience - Kumar, Narender; Bansal, Somendra; Gupta, Shalu; Yadav, Bhanwar Lal; Verma, Pradeep; Choudhary, Suresh (International Surgery Journal, 2019)
Background: Gall stone disease is the most common biliary pathology and frequently encountered in our daily practice. Patients with gall stone that experienced at least one attack of acute cholecystitis is defined as complicated gall stone disease (CGSD). Aim of this study was to find out the association between complicated gall stone disease and the metabolic syndrome. Methods: This prospective, observational study was done from 1st March 2017 to 30th November 2018 in department of general surgery, SMS hospital Jaipur. All patients with cholelithiasis admitted in general surgery department were included. Metabolic syndrome was defined by adult treatment panel III (ATP III) criteria. All patients were divided in two groups: complicated gall stone disease (CGSD) and uncomplicated gall stone disease (UGSD). Results: Mean age was 47.2 years in CGSD group and 46.7 year in UGSD group. Female to male ratio was 8.2:1 in CGSD group and 4:1 in UGSD. Metabolic syndrome was presented in 64 patients (58.2%) of CGSD group and 24 patients (21.8%) of UGSD patients, which was statistically significant (OR 4.986, CI 2.763-8.995, p value <0.001). Five components of metabolic syndrome were compared in both CGSD group and UGSD group. Lower serum HDL-C level and hyperglycemias was statistically significant in CGSD group as compared to UGSD group. Conclusions: Metabolic syndrome can be use to predict complicated gall stone disease. Hyperglycaemia and lower HDL-C associated with CGSD. One should be aware about possible metabolic syndrome background when dealing with gall stone disease patients.